MEMPELAJARI PENGGUNAAN TUNGKU LIMBAH KAYU SENGON (Parasaerianthes falcataria) UNTUK PENGERINGAN PAPANNYA - Tjutju Nurhayati (Jurnal Penelitian Hasil Hutan, 1991)
The  sengon wood waste fired stove was installed, to supily energy into certain length of circulating duct of the dryirlg chamber. The utilization of wet slabs  (moisture content  163.3  percent) in a wood stove produced drying air tempe- rature in the chamber at  30ᵒC.  When  jointing board waste  (moisture content  12.16  percent) was used to fire the stoue the drying temperature  of  70°.C was  achiued.The efficiency  of the wood waste fired  stoue was 39.46 percent, calculated on the basis of the energy produced by sengon wood waste burned, and the energy consumed by the drying  wood i.e 3.641 and 1.397 GJ.